Fungi from metal-polluted streams may have high ability to cope with the oxidative stress induced by copper oxide nanoparticles - Pradhan, Arunava (2015)
Increased commercialization of products based on metal oxide nanoparticles increases the likelihood that these nanoparticles will be released into aquatic environments, thus making relevant the assessment of their potential impacts on aquatic biota. Aquatic fungi are distributed worldwide and play a key role in organic matter turnover in freshwater ecosystems. The present study investigated the impacts of copper oxide spherical nanoparticles (CuO-NPs; <50nm powder, 5 levels 200mg/L) on cellular targets and antioxidant defenses in 5 fungal isolates collected from metal-polluted or nonpolluted streams. The CuO-NPs induced oxidative stress in aquatic fungi, as evidenced by intracellular accumulation of reactive oxygen species, and led to plasma membrane damage and DNA strand breaks in a concentration-dependent manner. Effects were more pronounced with a longer exposure time (3 d vs 10d). Under CuO-NP exposure, mycelia of fungi collected from metal-polluted streams showed less oxidative stress and higher activities of superoxide dismutase and glutathione reductase compared with fungi from nonpolluted streams. The latter fungi responded to CuO-NPs with a stronger stimulation of glutathione peroxidase activity. These findings may indicate that fungi isolated from metal-polluted streams had a greater ability to maintain the pool of reduced glutathione than those from nonpolluted streams. Overall, results suggest that populations adapted to metals may develop mechanisms to cope with the oxidative stress induced by metal nanoparticles. Environ Toxicol Chem 2015;34:923-930. (c) 2015 SETAC